Peran Bandar Udara terhadap Perkembangan Pariwisata Sumbawa Barat - Muhdisasami Gori Insani; Dhiani Dyahjatmayanti, S.TP., M.B.A., CRMP (Jurnal Manajemen Dirgantara, 2024)
Abstract Airport development in West Sumbawa plays an important role in supporting the local economy by creating many job opportunities, both at the airport itself and in supporting sectors such as transportation, accommodation, and restaurants, thus reducing the unemployment rate and improving the welfare of the surrounding community. The airport in West Sumbawa has a positive impact on tourism by increasing accessibility and the number of tourist visits. Data shows an increase in the number of domestic and foreign tourists from 770,344 in 2022 to 831,123 in 2023.